2015
DOI: 10.1037/pas0000058
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structure of the autism-spectrum quotient using Mokken scaling.

Abstract: Traits similar to those shown in autism spectrum condition (ASC) are apparent in relatives of individuals with ASC, and in the general population without necessarily meeting diagnostic criteria for an ASC. We assess whether the Autism-Spectrum Quotient (AQ), a self-report measure, has hierarchical properties using Mokken scaling. Hierarchical scales allow the presence of a latent trait to be identified by discovering whether and how many specific items form an ordered array along it. Data were collected from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…This result is in line with previous research using factor analysis (Austin 2005; Hoekstra et al 2008; Hurst et al 2007; Stewart and Austin 2009) and Mokken scaling (Stewart et al 2015). The hypothesized single latent variable is not consistent with the multidimensional nature of ASD, as expressed in the Diagnostic and Statistical Manual of Mental Disorders, DSM-5 (American Psychiatric Association 2013), or with the fact that Barron-Cohen (2001a) selected the AQ items from the domains in the “triad” of autistic symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in line with previous research using factor analysis (Austin 2005; Hoekstra et al 2008; Hurst et al 2007; Stewart and Austin 2009) and Mokken scaling (Stewart et al 2015). The hypothesized single latent variable is not consistent with the multidimensional nature of ASD, as expressed in the Diagnostic and Statistical Manual of Mental Disorders, DSM-5 (American Psychiatric Association 2013), or with the fact that Barron-Cohen (2001a) selected the AQ items from the domains in the “triad” of autistic symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, nine of these items (11, 13, 17, 22, 26, 34, 38, 44, and 47) are among the ten items that passed the Mokken scaling test on people with ASD (Stewart et al 2015). Hoekstra et al (2008), using CFA, found that the AQ consisted of two second-order factors, one of them including Social skill, Attention switching and Communication .…”
Section: Discussionmentioning
confidence: 99%
“…The AQ is a 50‐item self‐report measure that can dimensionalize behavioral traits typical of ASD in both university student and clinical samples [Baron‐Cohen et al, ; Stewart et al, ]. There are ten items devoted to each of five core domains: (a) social skills, (b) communication skills, (c) imagination, (d) attention to detail, and (e) attention switching/tolerance of change.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, MSA has increased in popularity in the fields of psychological and health assessment (e.g., Chou, Lee, Liu, & Hung, 2017; Lenferink et al, 2016; Murray, McKenzie, Murray, & Richelieu, 2014; Stewart, Allison, Baron-Cohen, & Watson, 2015; van den Berg, Paap, & Derks, 2013; Watson et al, 2012). MSA identifies scales that allow an ordering of individuals on an underlying scale using unweighted sum scores.…”
Section: Methodsmentioning
confidence: 99%